2010
DOI: 10.1016/j.jterra.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element method analysis of single wheel performance for a small lunar rover on sloped terrain

Abstract: The purpose of this study is to analyze the performance of a lugged wheel for a lunar micro rover on sloped terrain by a 2D discrete element method (DEM), which was initially developed for horizontal terrain. To confirm the applicability of DEM for sloped terrain locomotion, the relationships of slope angle with slip, wheel sinkage and wheel torque obtained by DEM, were compared with experimental results measured using a slope test bed consisting of a soil bin filled with lunar regolith simulant. Among the lug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Interest is increasing in the use of DEM models to improve the physical representation of off-road vehicle mobility in conditions where classical terramechanics models have difficulty (Li et al, 2012;Lichtenheldt and Schäfer, 2013;Nakashima et al, 2010;Smith and Peng, 2013;Smith et al, 2014;Wang et al, 2011). These studies have demonstrated that even 2-D DEM simulations with relatively simple particle geometries can provide useful qualitative representations of off-road vehicle mobility.…”
Section: Dem Models and Their Constraintsmentioning
confidence: 99%
“…Interest is increasing in the use of DEM models to improve the physical representation of off-road vehicle mobility in conditions where classical terramechanics models have difficulty (Li et al, 2012;Lichtenheldt and Schäfer, 2013;Nakashima et al, 2010;Smith and Peng, 2013;Smith et al, 2014;Wang et al, 2011). These studies have demonstrated that even 2-D DEM simulations with relatively simple particle geometries can provide useful qualitative representations of off-road vehicle mobility.…”
Section: Dem Models and Their Constraintsmentioning
confidence: 99%
“…The empirical method uses a practical measurement of soil strength with a specialized apparatus, such as a cone index (CI) [67], which is often used for an in situ prediction of vehicle traversability. The numerical method includes the finite-element method and discrete-element method that simulate soil deformation and vehicle-terrain interaction behavior with computer technology [72][73][74].…”
Section: Wheel-terrain Interaction Mechanicsmentioning
confidence: 99%
“…There is particular interest in the study of the behavior of the lunar regolith at low effective stresses, but such experiments are difficult to be performed in the laboratory due to the effect of terrestrial gravity and the models used should be scaled for Moon's gravitational acceleration (Cafaro et al, 2018;Hasan & Alshibli, 2010;Sture et al, 1998). Hence, cost-effective numerical modeling tools such as the discrete element method (DEM; after Cundall & Strack, 1979) have been implemented for the simulation of the lunar regolith and its interactions with rover vehicles (Knuth et al, 2012;Li et al, 2010;Nakashima et al, 2010Nakashima et al, , 2011Sullivan et al, 2011) and retaining structures (Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%